Epidemiological Aspects of Ascariasis and Associated Risk Factors Among Primary School Children in Lambata Community, Niger State, Nigeria During 2019-2020 - Gideon. I.A. Okoroiwu (Shiraz University of Medical Sciences, 2021)
Background: Ascaris worm, as one of the commonest helminthic infections, constitutes a major public health challenge and concern in the majority of developing countries. This study was conducted to assess the prevalence of Ascaris worm infection and its associated risk factors among primary school children in Lambata community to determine the prevalence of Ascaris infection, age, gender and associated risk factors among them to create awareness and effective management program. Methods: This is a cross-sectional descriptive study conducted between January 2019 and November 2020, in nine selected primary schools in Lambata community. A total of 303 stool samples were collected using random sampling to determine the prevalence of Ascaris infection using stool smear technique. The socio-demographic data were collected, using a structured interview questionnaire. The collected data were analyzed using simple percentages, OR and chi-square analytical methods. Results: Out of the 303 screened stool samples, 156 (51.5%)  had Ascaris infection. The most infected age-groups were 11-12 years old (73.8%; OR = 2.11) and 9-10 years (57.1%; OR = 2.01), while 6-8 year old subjects had the lowest rate (42.3%; OR = 1.00) of infection. Males (65.9%; OR= 2.00) were more infected than their female (39.9%; OR = 0.09) counterparts (P<0.05). Age, educational status / occupational status of parents, and defecation habits were significantly(P<0.05) associated with the prevalence of Ascaris infection. Conclusion: With the overall prevalence of 51.5% of Ascaris infection among the subjects, there is an indispensable need for health education promotion and coordinated de-worming of the primary school children in this community